Investigation of Islamic Financing Institutions in Middle Eastern Banking - KUMAR, Gaurav; MURTY, A.V.N.; SRINIVASA RAO, M.V.K. (Theoretical and Practical Research in Economic Fields, 2025)
Islamic finance institution is becoming increasingly important for MENA countries to finance their growth economically. Businesses respect people's social and religious beliefs while meeting their economic necessities. Even little is known about the factors influencing Islamic banking's expansion. I t offers a preliminary study of the relative significance of the major elements contributing to the expansion of Islamic banking in the area. By examining these banks' historical performance, we may use the financial crisis as an opportunity to analyze how Islamic banks contribute to the financial sector's resilience and inclusivity. The paper begins (Nizam, Kamarudin, Ali, & Hussain, 2024) with a brief background Islamic banking's development in the Sultanate of Oman, including how it connects to regional and foreign assets, liabilities, finance, and funding structures on the global Islamic financial markets, before examining Oman's current environment, examining the trends in the traditional financial sector and the rationale for adopting an Islamic financial system, as well as the long-term strategies the Sultanate of Oman has taken. Include how it might the layou t achieve the o bjective, c reate jobs for local people